PENGUKURAN EKSISTING BANGUNAN BALI DENGAN KETINGGIAN TERTENTU MELALUI METODE MODUL MATERIAL BANGUNAN, PHYTAGORAS DAN 3D MODELING STUDI KASUS BANGUNAN BALE BANJAR TENGANAN, BALI - MADE MAS SURYA WIGUNA; MADE SURYANATHA PRABAWA; I GUSTI AGUNG GEDE NODYA DHARMASTIKA (GANEC SWARA, 2024)
Balinese building concepts such as nawa sanga, tri mandala, Tri Angga and others are the basic concepts for Balinese buildings in the past and present. One concept that is often found in Balinese buildings is the tri angga concept, this concept reflects the feet, body and head of the building. Balinese buildings always have feet (foundation), body (wall) and head (roof) in each building, this has also become an official regulation of the Balinese government requiring buildings that want to have a building permit must have the Tri Angga concept. Many old Balinese buildings have the tri angga concept, but it is very unfortunate that old Balinese buildings have begun to be abandoned, dismantled and renovated to the current era. This problem is caused by the existing old Balinese buildings not having technical drawing data that can be used as a basis for buildings to be renovated. People prefer buildings to be dismantled and replaced with new buildings because it will be easier to build new buildings than to renovate old buildings without technical drawings. The problem of why old buildings do not have technical drawings is because the building measurement process requires many people and must be measured manually to the top of the building. Many costs will be incurred for one building resulting in this measurement process not being carried out. This problem becomes the mindset of the purpose of this research. The purpose of this research is to find the development of measurement methods, from manual methods to easy-to-do measurement coding systems. In this study, quantitative methods will be used with the help of material modules, Pythagorean formulas and 3D methods. The results of this study found that old Balinese buildings can be measured from the angle of the building, using material modules can calculate the distance from the structure, and the Pythagorean geometry formula is the key to this measurement scheme.